Simultaneous Human Immunodeficiency Virus-Hepatitis B-Hepatitis C Point-of-Care Tests Improve Outcomes in Linkage-to-Care: Results of a Randomized Control Trial in Persons Without Healthcare Coverage. (26th October 2015) - Bottero, Julie; Boyd, Anders; Gozlan, Joel; Carrat, Fabrice; Nau, Jean; Pauti, Marie-Dominique; Rougier, Hayette; Girard, Pierre-Marie; Lacombe, Karine
Abstract : In this randomized-control trial, conducted at a free clinic in France for predominately immigrant populations without healthcare, we demonstrate that simultaneous HIV/HBV/HCV point-of-care rapid testing improves screening outcomes. Increased awareness of infection status likely helped link these patients to care. Abstract: Background. In Europe and the United States, more than two thirds of individuals infected with hepatitis B virus (HBV) or hepatitis C virus (HCV) and 15%–30% of human immunodeficiency virus (HIV)-positive individuals are unaware of their infection status. Simultaneous HIV-, HBV-, and HCV-rapid tests could help improve infection awareness and linkage-to-care in particularly vulnerable populations. Methods. The OptiScreen III study was a single-center, randomized, control trial conducted at a free clinic ("Médecins du Monde", Paris, France). Participants were randomized 1:1 to receive 1 of 2 interventions testing for HIV, HBV, and HCV: standard serology-based testing (S-arm) or point-of-care rapid testing (RT-arm). The main study endpoints were the proportion of participants who became aware of their HIV, HBV, and HCV status and who were linked to care when testing positive. Results. A total of 324 individuals, representing mainly African immigrants, were included. In the S-arm, 115 of 162 (71.0%) participants performed a blood draw and 104 of 162 (64.2%) retrieved their test result. In comparison, 159 of 162 (98.2%) of participants randomized to the RT-arm obtained their results ( P < .001). Of the 38 (11.7%) participants testing positive (HIV, n = 7; HBV, n = 23; HCV, n = 8), 15 of 18 (83.3%) in the S-arm and 18 of 20 (90.0%) in the RT-arm were linked-to-care ( P = .7). In post hoc analysis assuming the same disease prevalence in those without obtaining test results, difference in linkage-to-care was more pronounced (S-arm = 60.0% vs RT-arm = 90.0%; P = .04). Conclusions. In a highly at-risk population for chronic viral infections, the simultaneous use of HIV, HBV, and HCV point-of-care tests clearly improves the "cascade of screening" and quite possibly linkage-to-care.